Caracterização gênica para uma anomalia de Eucalyptus em fase inicial de desenvolvimento - Fuchs, Maria Cecília Perantoni [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Eucalyptus is one of the most important genus in worldwide forestry culture. For this reason forest improvement programs are developed aiming the increase of productivity, the introduction of desirable traits and the reduction of environmental impacts. However deleterious traits can be incorporated in certain crossings through the recurrent improvement cycles either by biparental inbreeding or by segregation of the heterozygous loci. Anomalies are an example of this deleterious effect and they can cause losses in seedling production, productivity and delays in the elite genotypes development. Thus, the identification and characterization of genes related to the anomalies are very important in forest improvement programs. In a controlled cross between two Eucalyptus grandis individuals, the Suzano Papel and Celulose SA company has detected an anomaly with Mendelian segregation ratio of 3 (normal) :1 (abnormal) in the progeny. Abnormal seedlings die in a few months and show significant difference in some morphological characteristics, such as height, stem-base diameter, dimensions and shape of leaf lamina, and number of branches. Previous studies allowed the identification of a molecular marker related to the anomaly that showed identity with Bet v1 superfamily genes, PR10 family (pathogenesis-related protein 10). However, it was not clear the involvement of this gene family in the anomaly. In this scenario, the present study aimed to identify and characterize the genes involved in the detected anomaly. Genes and metabolic pathways, differentially expressed between the contrasting phenotypes, showed high activity of process related to defense response in abnormal plants. These results suggest that the anomaly is caused by the inappropriate activation of the immune system of the plant (autoimmune response) associated with genetic incompatibility. The gene families of thaumatin-like proteins, Bet v1 proteins, and chitinase class I proteins ...

O Eucalyptus é um dos gêneros mais importantes no setor florestal mundial. Por esse motivo, programas de melhoramento genético florestal são desenvolvidos no intuito de aumentar a produtividade, introduzir características desejáveis e reduzir impactos ambientais. No entanto, características deletérias podem ser incorporadas em determinados cruzamentos nos ciclos de melhoramento, seja por endogamia biparental ou segregação de loci heterozigóticos. As anomalias são um exemplo deste efeito e podem acarretar perdas na produção de mudas, na produtividade e atrasos no desenvolvimento de genótipos elite. Portanto, a identificação e caracterização de genes relacionados às anomalias são muito importantes nos programas de melhoramento. Ao realizar um cruzamento controlado entre dois indivíduos de Eucalyptus grandis, a empresa Suzano Papel e Celulose detectou uma anomalia com segregação mendeliana de 3 (normais) :1 (anormais) na progênie. As plântulas anômalas morrem em poucos meses e diferem significativamente em algumas características morfológicas, como altura, diâmetro da base do caule, dimensões e forma do limbo foliar e número de ramificações laterais. Estudos prévios permitiram identificar uma marca molecular ligada à anomalia que apresentou identidade com genes da superfamília Bet v1, família PR10 (pathogenesis-related protein 10). No entanto, não era claro o envolvimento desta família gênica no desenvolvimento da anomalia. Neste cenário, o presente trabalho teve como objetivo a identificação e caracterização dos genes envolvidos na anomalia detectada. Genes e vias metabólicas, diferencialmente expressos entre os fenótipos contrastantes, demonstraram elevada atividade em processos relacionados à resposta de defesa nas plantas anormais. Tais resultados sugerem que a anomalia é causada pela ativação inadequada do sistema imune da planta (resposta autoimune) associado à incompatibilidade ...
Gene characterization of an Eucalyptus anomaly in the early stage of development
Keywords: Eucalipto - Melhoramento genético; Expressão gênica; Genetica vegetal; Acido ribonucleico; Eucalyptus - Breeding